Placental weights of neonates born with symptomatic congenital syphilis - Pillay, Shakti; Horn, Alan R.; Tooke, Lloyd (Frontiers in Pediatrics, 2023)
Background: Syphilis during pregnancy remains an important global health concern causing miscarriage, stillbirth, preterm birth and neonatal death. As part of the fetal infection, placental changes occur which may include a heavier placenta than expected.Methods: A cohort of 50 neonates with symptomatic congenital syphilis has previously been described. This cohort was admitted to Groote Schuur neonatal unit in Cape Town South Africa from 2011-2103. For this study, the placental weights of the neonates were analysed and compared to population based placental centiles.Results: There was data for 37 placentae. Heavy placentae (>90 th centile) occurred in 76% of placentae in the study. All 6 infants with birth weights ≥2500g had heavy placentae. There was no correlation between placental centile and death.Conclusion: Heavy placenta are an important and frequent finding with symptomatic congenital syphilis, especially in the larger neonates.